Epidemiological and clinicopathological characteristics of colorectal cancer patients in tertiary hospital in West Java - Kiki Lukman; Arrayyan Muhammad; Mohammad Ghozali; Prapanca Nugraha; Yunia Sribudiani; Bistamy Muhammad Nursabur (Elsevier, 2024)
Problem considered: Colorectal cancer (CRC) is the third most frequently diagnosed type of cancer in Indonesia, accounting for around 8.5% of cancer cases. This study aims to know the epidemiological and clinicopathological characteristics of CRC patients in Tertiary Hospital in West Java. Methods: This study was a cross-sectional study. All the data were obtained from Hasan Sadikin General Hospital CRC Registry from November 2021 until May 2023. Results: 208 colorectal cancer patients were analyzed. The average age at diagnosis was 52,9 (52 ± 13.1) with 61% diagnosed over 50. More females (51%) were diagnosed. Smoking history included 37.5% active smokers and 41.8% passive exposure. Nutritionally, 65.8% were normal weight, 30.7% underweight, and 5% overweight. The most common presenting symptoms were constipation (49%) and rectal bleeding (38%). Stage III and IV were diagnosed in 77% of patients. Left-sided colon tumors (85%) were most frequent, with adenocarcinoma not otherwise specified (98%) being the dominant histology. Bowel obstruction (68%) was the most common complication. Conclusion: CRC in Hasan Sadikin General Hospital was frequently diagnosed at a late stage, with a relatively high percentage of patients were below 50 years. Left-sided CRC and histological types of adenocarcinoma not otherwise specified were still the most common pathological features of CRC. Future research is needed to discover the potential multifactorial causes of this phenomenon.